2003
DOI: 10.1080/13636820300200232
|View full text |Cite
|
Sign up to set email alerts
|

Tourism degree internships: a longitudinal study

Abstract: This case study briefly reviews the development of tourism degrees in the United Kingdom before considering the experiences obtained by students on year-long internship programmes over a period of 8 years. Verbatim confidential comments, from students, are provided and specific transferable skills discussed. Whilst some skills can be developed during the course of an academic programme, it is argued that the internship period can provide a wider range and help clarify career intentions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 32 publications
(26 reference statements)
0
59
0
3
Order By: Relevance
“…It is suggested that some skills are essential for employment and, arguably, the internship is the most appropriate vehicle for their acquisition. Certainly, for the development of practical skills, the internship is crucial (Busby, 2003). However, research on internship programs has shown significant gaps in expectations between industry and hospitality educators (Downey & De Veau, 1988).…”
Section: Tourism Educationmentioning
confidence: 99%
“…It is suggested that some skills are essential for employment and, arguably, the internship is the most appropriate vehicle for their acquisition. Certainly, for the development of practical skills, the internship is crucial (Busby, 2003). However, research on internship programs has shown significant gaps in expectations between industry and hospitality educators (Downey & De Veau, 1988).…”
Section: Tourism Educationmentioning
confidence: 99%
“…However, after discussion with colleagues and senior management and with feedback from students, this option was rejected. Indeed, while several authors highlight the benefits of year long placements (or internships) (see for example Busby, 2003;Busby, Brunt & Baber, 1997;Leslie & Richardson, 2000), citing: broadening knowledge, creating awareness, influencing career choice, including the development of students both personally and professionally in "adherence to business values" (Tribe, 2001), this relates predominantly to undergraduate rather than postgraduate study. Indeed, findings suggest the benefits of offering industry connection are in fact outweighed by the additional year required to complete the programme of study at postgraduate level.…”
Section: Extending Current Msc To a 2-year Programme With 1-year Placmentioning
confidence: 99%
“…Empirical studies also show that graduates with internship experience receive a job offer more quickly than those without (Knouse, Tanner, & Harris, 1999;Kwok, Adams, & Price, 2011). Indeed, employers place more emphasis on the communication skills and critical thinking ability of job candidates, all of which can be fostered during internship, than on academic performance alone (Busby, 2003;Knouse & Fontenot, 2008;Lee, 2008). On the other hand, internship experiences enhance students' confidence (Hejmadi et al, 2011;Ko, 2008).…”
Section: Benefits and Threats Of Internshipmentioning
confidence: 99%